Sudan’s Humanitarian Crisis and The War of Military Elites: Prospects for a Resolution - Mukhtar Imam (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
Sudan has been facing a prolonged humanitarian crisis exacerbated by ongoing conflicts between military elites. This study aims to analyze the root causes of Sudan’s humanitarian crisis, the role of military elites in perpetuating the conflict, and the prospects for a sustainable resolution. Using a qualitative approach with the literature review method, this research examines various secondary sources, including official reports, academic journals, and historical accounts. The findings suggest that Sudan’s crisis is deeply rooted in historical injustices, political instability, economic inequality, and military dominance. The analysis highlights how military elites have exploited state resources and engaged in armed conflicts to maintain power, further worsening the humanitarian situation. Possible solutions include international mediation, grassroots movements, institutional reforms, and economic development to foster long-term peace. By providing a comprehensive understanding of Sudan’s crisis, this study offers insights into potential strategies to address the ongoing humanitarian disaster.